The Impact of Financial Literacy Programs on Personal Finance Management : A Case Study of Ahmedabad, Gujarat - Dr. Shivali Shah (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
In an increasingly complex financial environment, financial literacy has emerged as a critical skill for ensuring individual financial well-being and economic inclusion. This study investigates the impact of financial literacy programs on personal finance management in Ahmedabad, Gujarat, focusing on behaviors such as budgeting, saving, and financial decision-making. Using a quantitative research design, data were collected from 180 adult respondents via a structured questionnaire. The results revealed a statistically significant improvement in financial behavior among individuals who had participated in financial literacy programs, supporting the positive role these interventions play in promoting responsible financial habits. However, contrary to expectations, the study found a slight negative association between program participation and financial decision-making scores, suggesting potential gaps in the practical application or perceived confidence in financial decisions post-training. These findings highlight both the strengths and limitations of current financial literacy efforts and underscore the importance of context-sensitive, behavior-focused financial education. The study concludes with practical recommendations for policymakers, educators, and community organizations to enhance the design, reach, and effectiveness of financial literacy programs in urban India.